Personalised Learning for the Student-Consumer - Partington, Angela (Frontiers in Education, 2020)
This paper (written in British English) seeks to contribute to the development of personal tutoring as a key aspect of learner-centric pedagogy, in response to the changing profile of Higher Education (HE) students, especially in terms of the social and cultural capital which they bring with them, which shapes what and how they want to learn, and the marketisation of HE in the United Kingdom. It will challenge some of the prevailing views about student engagement, in order to contribute to the development of learning cultures which are relevant to the 21st century (McWilliam, 2010), and to enable personal tutoring to add value to the experience of all students, by explicitly recognising the diverse range of competencies and literacies which students bring to their studies, and enabling students to use these resources to co-create their learning experience. This requires the development of personal tutoring as a means of challenging the hidden curriculum, thereby enabling universities to adapt to students’ needs (rather than, or as well as, requiring students to adapt to universities’ expectations), through the recognition of personal tutoring as a specific area of academic expertise, and elevating its importance and its contribution to student success, and by enabling it to contribute to the development of personalised learning (not just providing individualised support). It will be argued that the development of effective personal tutoring, which reflects the diversity of C21st students, requires an approach which transcends the binary opposition between ‘student as partner’ (SaP) and ‘student as consumer’ (SaC), which creates a mono-cultural approach to student engagement, by recognising that students are active consumers, already engaged in the development of their own identities, and that the co-creation of their learning experience is one of the ways they do this. This would enable personal tutoring to play a central role in supporting all students to develop their own reflexivity, enabling them not only to pursue a professional career, (and enabling businesses to create a more diverse workforce), but to shape the future of the industries in which they will work.